Changes in Microbial Diversity and Nutritional Components of Mare Milk Before and After Traditional Fermentation - Li, Qinyu; Zhao, Yulian; Siqin, Bateer; Xilin, Tuya; Zhang, Na; Li, Minhui (Frontiers in Sustainable Food Systems, 2022)
The formation and quality of nutrients before and after fermentation depends on microbial community dynamics. In this study, the nutrients and microflora of mare milk were studied before and after traditional fermentation. To achieve this goal, ultra-performance liquid chromatography-mass spectrometry and Illumina MiSeq sequencing were used to study the changes in the main nutrients and microbial communities, respectively, before and after mare milk traditional fermentation. A total of 81 nutrients were identified before and after the fermentation of mare milk into koumiss; among these, 6 compounds [citraconic acid, 6-hydroxycaproic acid, creatine, adenine, d-(+)-proline, and histamine] were differentially upregulated. Histamine levels increased after traditional fermentation, whereas Lactobacillus, Dekkera, and Acetobacter grew rapidly and became the dominant microorganisms in the fermentation process. These three genera were positively correlated with creatine and proline levels, whereas Lelliottia was negatively correlated with citraconic acid and proline levels. Prediction of the functions of bacteria and fungi in the mare milk before and after fermentation included carbohydrate metabolism, cofactors and nutrition, and plant pathogens. The results of this study provide new insights into the formation of nutrients in koumiss; it is important to study changes in bacteria and fungi before and after traditional fermentation.